Simplify 18x - [-12y - {9z - (7y - 6x + 2z)}]
Answers
Answered by
1
This pic may help you for your question
Attachments:
![](https://hi-static.z-dn.net/files/dd0/b64dbeafafea70bcd8eaf1e28d388f6e.jpg)
Answered by
26
Answer:
Given,
18x-[-12y - {9z - (7y - 6x +2z)}]
Step-by-step explanation:
So,
=> 18x -[-12y - {9z - (7y - 6x +2z )}]
=> 18x -[-12y - {9z - 7y + 6x + 2z }]
=> 18x -[-12y - {6x - 7y + 11z }]
=> 18x -[-12y - 6x + 7y - 11z ]
=> 18x -[-6x - 5y - 11z ]
=> 18x + 6x + 5y + 11z
=> 24x + 5y + 11z
Hence,
It is the answer 24x + 5y + 11z
Similar questions
Math,
2 months ago
Computer Science,
2 months ago
English,
5 months ago
Hindi,
1 year ago
Math,
1 year ago